Photocatalytic Activity of Hierarchically Nanoporous BiVO4/TiO2 Hollow Microspheres (Journal of Fiber Bioengineering and Informatics, 2012)
The hollow microspheres containing monoclinic scheelite BiVO_4 and anatase TiO_2 nanocrystals wereeasily prepared through a simple one-step template-free method. Bi(NO_3)_3 • 5H_2O and NH_4VO_3 were usedas BiVO_4 precursor and (NH_4)_2TiF_6 as TiO_2 precursor to produce the target products in the presence ofglucose under the high temperature pyrolysis. The products were characterized with SEM, XRD, TEMand UV-vis DRS. The as-prepared hollow microspheres showed high photocatalytic activity, which wasdemonstrated by degradation of acetic acid solution under visible-light irradiation (λ › 420 nm).